“All this Regulatory Uncertainty in the Air”: The Indispensability of Public Hearings in Guarding and Guiding Public Deliberation - Carroll, Jaclyn; Bsumek, Pete (Frontiers in Communication, 2021)
Using the case of the proposed “Cyprus Creek Power Station” in Surry County, Virginia (2009-2013), the authors revisit environmental decision-making scholarship suggesting that the Surry County case illuminates theoretical limitations of existing work. Both community organizers and scholars ought to be attuned to these limitations. Scholarship on environmental decision-making and public participation processes has emphasized impassable barriers to representation, particularly for low-income and development-targeted communities. Public participation processes are often dismissed as forms of Decide, Announce, Defend (DAD). We offer the Surry County case to highlight limitations of this scholarship, and to point to several features of small town, community democracy that ought to be accounted for in environmental decision making and public participation scholarship.